Ratio of height to thyromental distance: a comparison with Mallampati and Upper lip Bite test for predicting difficult intubation in Pakistani population - Saman Tauheed Ali; Khalid Samad; Syed Amir Raza; Muhammad Qamarul Hoda (Journal of the Pakistan Medical Association, 2021)
Objectives: We conducted this study to compare the accuracy of three diagnostic tests; ratio of height to thyromental distance (RHTMD), Modified Mallampati Test (MMT) and Upper Lip Bite Test (ULBT) in predicting difficult laryngoscopy using Cormack and Lehane grade as gold standard. Methods: This study was conducted in Aga Khan University Hospital, Karachi. Based on calculated sample size, 383 patients who required endotracheal intubation for elective surgical procedures were enrolled with consecutive sampling techniques during August 2014 to August 2015 for this cross-sectional study. Primary investigator used RHTMD, ULBT, and MMT for assessing the airway and correlated with laryngoscopic view. Results: A total of 383 patients were incorporated in this research, out of which 59(15.4%) classified as difficult laryngoscopy based on Cormack and Lehane (CL) grading. Sensitivity, specificity, positive predictive value, negative predictive value and accuracy of RHTMD (84.7%, 90.1%, 60.9%, 97%, 89.3%) and ULBT (83.1%, 89.2%, 58.3%, 96.7%, 88.3%) values were highest as compared to MMT (30.5%, 84.3%, 26.1%, 86.9%, 79.9%). The area under a receiver-operating characteristic curve (AUC of ROC curve) for ULBT and RHTMD was significantly more than for MMT (P<0.01). RHTMD and ULBT both are acceptable alternatives for prediction of difficult laryngoscopy as a simple, single bed-side test. Continuous...